28.1k views
3 votes
H=vt+1/2gt^2 solving for G
GIVING BRAINLISEST

2 Answers

4 votes

Answer:

g =
(2(h - vt))/(t^2)

Explanation:

Given

h = vt +
(1)/(2) gt² ( subtract vt from both sides )

h - vt =
(1)/(2) gt² ( multiply both sides by 2 to clear the fraction )

2(h - vt) = gt² ( divide both sides by t² )


(2(h-vt))/(t^2) = g

User Wickjon
by
5.3k points
1 vote

Answer:


\displaystyle g = (2(h-vt))/(t^2)

Explanation:

We are given the equation:


\displaystyle h = vt+(1)/(2)gt^2

And we want to solve for g, the acceleration due to gravity.

Proceed with algebra:


\displaystyle \begin{aligned} h & = vt + (1)/(2)gt^2 \\ \\ h - vt & = (1)/(2)gt^2 \\ \\ gt^2& = 2(h-vt) \\ \\ g &= (2(h-vt))/(t^2)\end{aligned}

In conclusion:


\displaystyle g = (2(h-vt))/(t^2)

User Crew HaXor
by
5.0k points